METODE CEPAT IDENTIFIKASI JARINGAN IRIGASI TERSIER DALAM PROSES PERBAIKAN IRIGASI - purwadinata, haryono; Ramadhani, Fadhlullah (Informatika Pertanian, 2016)
The availability of water can not be separated from good tertiary irrigation network, apart from the available Secondary and Primary networks and also irrigation dams. Apart from funding, monitoring of JIT (Tertiary Irrigation Network) during the development and implementation is important. Identification of JIT condition is necessary for repairs, and problem frequently arise is the lack of rapid and accurate report from monitoring the condition. A rapid identification method that is simple, fast and accurate, provides an alternative in implementing the irrigation network monitoring. With a simple device that is Android-based mobile phone, equipped with a variety of applications, such as GPS Test, Open camera, GPS Photo Viewer and Photo folders, it is easier in monitoring of JIT. Results of monitoring in West Lombok using rapid method as an alternative, provided an option, better than the old method, with garmin gps, pictures with coordinates that can be sent directly, via social media, so that monitoring can be viewed simultaneously in the field and in the central office, monitoring information did not require a long time in the reports, and impact evaluation could be faster.